Study on the Liability Structure and Profitability of the Banking Industry in the Asia-Pacific Region - WANG, Jing; SELAMAT, Aslam Izah; ASHHARI, Zariyawati Mohd; YAHYA, Mohamed Hisham Dato Hj (Theoretical and Practical Research in Economic Fields, 2024)
This study investigates the relationship between the profitability and liability structure of commercial banks within six Asia-Pacific countries (China, India, Australia, Japan, South Korea, and Singapore), by analyzing annual data from BankFocus for 691 banks from 2013 to 2022. The central focus of this research is to explore the impact of banks' liability structure - highlighting passive liabilities, interbank borrowing, and bond issuance - on critical profitability indicators, specifically Return on Equity (ROE) and Tier 1 Ratio (T1R). This research employs panel data analysis alongside Hausman-tested. Our findings discover the roles that passive liabilities and bond issuance play in strengthening banks' core capital and enhancing profitability. Additionally,  the impact of bank deposit and borrowing services on profitability and capital across developed and developing nations within the Asia-Pacific region. The study offers practical suggestions for the banking sector, emphasizing the need for improved liability management to boost profitability. These recommendations, backed by thorough empirical research and robustness checks, provide a solid foundation for strategic policy and planning in the sector.